Dual-colour imaging of RNAs using quencher- and fluorophore-binding aptamers - Arora, Ankita; Sünbül, Murat; Jäschke, Andres (Nucleic acids research, 2015)
Abstract. In order to gain deeper insight into the functions and dynamics of RNA in cells, the development of methods for imaging multiple RNAs simultaneously